INTRAPRENEURSHIP AT A STATE-OWNED ENTERPRISE IN CHINA (An explorative and qualitative study in a state-owned enterprise in China) - Vermeulen, Anselm A.M. (Digital Repository of Theses, 2022)
The purpose of the dissertation is to get a better insight into the needs of an education program related to intrapreneurship at a State-Owned Enterprise in China and based on these needs to come up with a customized education program for a specific State-Owned Enterprise in China and ultimately to improve intrapreneurial activities at conservative companies in China. Although there are many issues related to intrapreneurship, the following were selected for the literature review: the role of foreign direct investment in SOEs, the role of mixed ownership at SOEs, the role of incentive systems at SOEs, the effect of bureaucracy at SOEs and personality characteristics and their impact on intrapreneurial activities at SOEs. A conceptual framework was made to visualise the structure and flow of this dissertation. Besides the extensive literature review about the role of foreign investment, the role of mixed ownership, the role of incentive systems at SOEs, the effects of bureaucracy at SOEs and personality characteristics and their impact on intrapreneurial activities at SOEs, a substantial part of the literature review is about intrapreneurship in general, about communication in China and about how to conduct research at a SOE. The company where both the survey and the interviews were conducted was CRRC, a major State-Owned Enterprise in China. The survey was answered by 32 people working at CRRC and the interviews were done with 8 people working at CRRC. Both the survey and the interviews gave a clear understanding for the need of an intrapreneurial mindset at the company and more specifically helped setting up an educational program to improve intrapreneurial activities at the State-Owned Enterprise. A major constraint of this research is that the findings are limited to CRRC and to optimize the educational program for a wider use more research needs to be conducted at other State-Owned Enterprises in China as well. Another constraint is that the researcher had to select inputs to use for his research. This selection was based on relevance to the research and were specifically, current level of intrapreneurship at state-owned enterprise, ownership issues at SOE, bureaucracy at SOE, incentives and intrapreneurship at SOE ad personality characteristics and their impact on intrapreneurship at SOE. Other inputs like management and leadership styles, the role of government and other institutions, tax incentives, financial strength of company and cultural dimensions could have been considered as well and could be subject to future research. This dissertation can be used by any conservative company in China to engage employees and improve intrapreneurship in general and can form a basis for a more specific and customized program later.